A mnemonic topology of the eighteen days in Egypt (25th January-11th February 2011) - Verderi, Sara (AUC Knowledge Fountain, 2015)
The aftermath of the eighteen days in Egypt constitutes a moment in which it is possible to study the entanglement between evolving political imaginations, techniques of governability and capital processes of restructuring. Focusing on the stories of activists who took part in the 25th January uprising, this thesis examines the conflicting representations thriving to establish a mnemonic "truth" about a moment of political transformation. In using memory as a methodological lens, this thesis proposes to consider the operational aspect of memory, thinking about memory as a usable knowledge in the present. This approach to memory re-discusses its use as category of experience by putting the accent on the way in which the 'event revolution' prolongs in activists’ lives. By tracing a mnemonic topology, the purpose of this thesis is that of looking at how Tahrir's eighteen days are remembered differently not only among activists in Cairo but also in different socio-geographical contexts. Throughout the stories of interlocutors in Cairo, Aswan in Upper Egypt and Damanhour in the Nile Delta this thesis examines different re-elaborations of temporalities and representational politics, part and parcel of 'revolution' nomenclature and the way in which social change is imagined. This thesis will explore how women activists have been variously thinking about 'revolution' in the light of their experiences in the first phase of the uprising and how the memory of the 'event' is translated and mediated into their everyday lives. In this context, the multiplicities of desires formulated varies according to class and geography. Coming from genuine desire to give a material form to emerging political subjectivities, the textual production of the three feminist NGOs taken into analysis intersects with processes of commercialization of 'trauma' and commodification of the figure of the harassed woman, its production and consumption within neoliberal terms.